A Socially Aware Routing Based on Local Contact Information in Delay-Tolerant Networks. (1st July 2014) - Kim, Chan-Myung; Han, Youn-Hee; Youn, Joo-Sang; Jeong, Young-Sik
Abstract : In delay-tolerant networks, network topology changes dynamically and there is no guarantee of continuous connectivity between any two nodes. These features make DTN routing one of important research issues, and the application of social network metrics has led to the design of recent DTN routing schemes. In this paper, we propose an efficient routing scheme by using a node's local contact history and social network metrics. Each node first chooses a proper relay node based on the closeness to the destination node. A locally computed betweenness centrality is additionally utilized to enhance the routing efficiency. Through intensive simulation, we finally demonstrate that our algorithm performs efficiently compared to the existing epidemic or friendship routing scheme.